2018
DOI: 10.4162/nrp.2018.12.6.527
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a school-based culinary nutrition education program on vegetable consumption behavior, intention, and personal factors among Korean second-graders

Abstract: BACKGROUND/OBJECTIVESVeggiecation was developed to improve children's vegetable consumption through classroom lecture and cooking activities. In this study, we explored potential determinants of vegetable consumption behavior and intention, and examined the impact of Veggiecation on vegetable consumption behavior, intention and personal factors among Korean children.MATERIALS/METHODSThe 4-week Veggiecation program was implemented for second-graders in South Korea (35 children in the intervention group, 36 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Study populations varied from 77 to 2519. Successful interventions included school gardens (n 9) (41)(42)(43)(44)(45)(46)(47)(48)(49) , food provision (n 5) (50)(51)(52)(53)(54) , taste testing (n 8) (55)(56)(57)(58)(59)(60)(61)(62) , cooking lessons (n 10) (63)(64)(65)(66)(67)(68)(69)(70)(71)(72) and other multiple component interventions which included additional activities (n 10) (73)(74)(75)(76)(77)(78)(79)(80)(81)(82) such as farmer visits, Harvest of the Month Program or a nutrition education card game.…”
Section: Experiential Interventions and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study populations varied from 77 to 2519. Successful interventions included school gardens (n 9) (41)(42)(43)(44)(45)(46)(47)(48)(49) , food provision (n 5) (50)(51)(52)(53)(54) , taste testing (n 8) (55)(56)(57)(58)(59)(60)(61)(62) , cooking lessons (n 10) (63)(64)(65)(66)(67)(68)(69)(70)(71)(72) and other multiple component interventions which included additional activities (n 10) (73)(74)(75)(76)(77)(78)(79)(80)(81)(82) such as farmer visits, Harvest of the Month Program or a nutrition education card game.…”
Section: Experiential Interventions and Characteristicsmentioning
confidence: 99%
“…Ten (63)(64)(65)(66)(67)(68)(69)(70)(71)(72) of the eleven studies on cooking lesson interventions resulted in successful outcomes for self-efficacy and confidence in cooking skills. Cooking programme duration varied between three lessons (68) , four lessons (65,72) , five lessons (67,70) , eight lessons (63) and ten lessons (64,66,69,71) , with three also including classroom nutrition education (67,(69)(70)(71)(72) . Notably, the four studies that measured food consumption (65,66,68,70) reported improvements in dietary intake following participation in cooking classes.…”
Section: Experiential Interventions and Characteristicsmentioning
confidence: 99%
“…Bai et al [23] Compared to the control group, the Veggiecation intervention led to the following: + Higher (p < 0.001) self-reported scores for behavior and intention in relation to vegetables. + Higher (p < 0.001) self-reported scores for attitude about, and preference for, vegetables.…”
Section: Table 2 Summary Of Key Results From School-based Culinary Interventions For 5-12-year-old Childrenmentioning
confidence: 97%
“…Hence, it is important to measure vegetable and fruit consumption in this population, and to design methods to increase the consumption of these food groups. There are reports indicating that school nutrition programs can improve children's vegetable consumption and intention, as well as their preference, attitude, and self-efficacy [ 4 5 ]. Various food education (FE) strategies may be implemented to encourage healthy eating habits among teenagers.…”
Section: Introductionmentioning
confidence: 99%